The Influence of Digital Media (Webinars and Online Training) on the Capacity Development of Agricultural Extension Workers - Kharisma Dewi; Achmad Faqih; Siti Aisyah (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
This study aims to analyze the effect of digital media—specifically webinars and online training—on the capacity development of agricultural extension workers. A quantitative approach was employed using a survey method, with data analyzed through multiple linear regression using IBM SPSS. Digital media were measured through seven sub-variables: accessibility, content quality, interactivity, utilization, ease of use, effectiveness, and information reach and distribution. The results indicate that all digital media variables simultaneously have a significant effect on the capacity development of extension workers. However, partial analysis reveals that only interactivity, ease of use, and effectiveness have a positive and significant influence, while the other variables show no significant effect. These findings suggest that the effectiveness of digital media in enhancing extension capacity is determined not merely by access or information availability but by the quality of learning processes and the practical relevance of materials. The study concludes that digital media should be designed as interactive, user-friendly, and effective learning tools. The implications of this study provide a basis for improving digital training policies and strategies within agricultural extension systems.